Phosphate-related genomic islands as drivers of environmental adaptation in the streamlined marine alphaproteobacterial HIMB59 - Carmen Molina-Pardines; Jose M. Haro-Moreno; Mario López-Pérez (mSystems, 2023)
ABSTRACT Prokaryotic species are composed of multiple clonal lineages coexisting in the same habitat. In recent years, understanding the maintenance of this high intraspecific genetic diversity in asexual microorganisms has been a challenge for microbial ecology. In this study, we investigated the potential ecological role of this genomic heterogeneity in the marine HIMB59 clade. The metagenomic recruitment revealed the presence of three main genomospecies with different ecological distribution patterns within the two defined families. Genomic analysis revealed the presence of a flexible genomic island conserved throughout the order at the same position in the genome and related to phosphate (P) metabolism. The different versions of this island showed a distribution correlated with the concentration of P in the environment but not with the phylogeny at the genomospecies level. At high P availability (>0.5 µM), HIMB59 cells had only the high-affinity phosphate transporter operon (PstSCAB and PhoU). Under conditions of higher P scarcity (<0.05 µM), the cells presented a higher number of genes for the acquisition of P groups from other sources such as organic molecules and their storage. Additionally, in oligotrophic regions exhibiting extreme P depletion, such as the Mediterranean Sea, we found a second flexible genomic island related to phosphonate catabolism to supply metabolic P requirements. These results suggest that these microbes maintain in natural populations a gene pool with an equivalent biological function that allows them to respond to variations in certain micronutrients, creating ecologically distinct lineages within each species.IMPORTANCEThese results shed light on the evolutionary strategies of microbes with streamlined genomes to adapt and survive in the oligotrophic conditions that dominate the surface waters of the global ocean. At the individual level, these microbes have been subjected to evolutionary constraints that have led to a more efficient use of nutrients, removing non-essential genes named as “streamlining theory.” However, at the population level, they conserve a highly diverse gene pool in flexible genomic islands resulting in polyclonal populations on the same genomic background as an evolutionary response to environmental pressures. Localization of these islands at equivalent positions in the genome facilitates horizontal transfer between clonal lineages. This high level of environmental genomic heterogeneity could explain their cosmopolitan distribution. In the case of the order HIMB59 within the class Alphaproteobacteria, two factors exert evolutionary pressure and determine this intraspecific diversity: phages and the concentration of P in the environment.